2022
DOI: 10.3390/ijms23084452
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Synthesized Nanoparticles in Developing Plant Abiotic Stress Resilience: A New Boon for Sustainable Approach

Abstract: Agriculture crop development and production may be hampered in the modern era because of the increasing prevalence of ecological problems around the world. In the last few centuries, plant and agrarian scientific experts have shown significant progress in promoting efficient and eco-friendly approaches for the green synthesis of nanoparticles (NPs), which are noteworthy due to their unique physio-biochemical features as well as their possible role and applications. They are thought to be powerful sensing molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(13 citation statements)
references
References 117 publications
(148 reference statements)
1
12
0
Order By: Relevance
“…We also found an obvious variation in the effectiveness of 25, 50, 75, and 100 mg/L concentrations of Co 3 O 4 Nbs. However, no lethal effects were observed even at higher concentrations . It was also found that Co 3 O 4 Nbs synthesized by green methods did not show noxiousness at higher concentrations and gave a positive response to plant growth and metal-stress alleviation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found an obvious variation in the effectiveness of 25, 50, 75, and 100 mg/L concentrations of Co 3 O 4 Nbs. However, no lethal effects were observed even at higher concentrations . It was also found that Co 3 O 4 Nbs synthesized by green methods did not show noxiousness at higher concentrations and gave a positive response to plant growth and metal-stress alleviation.…”
Section: Resultsmentioning
confidence: 99%
“…However, no lethal effects were observed even at higher concentrations. 66 It was also found that Co 3 O 4 Nbs synthesized by green methods did not show noxiousness at higher concentrations and gave a positive response to plant growth and metal-stress alleviation. Mean squares obtained after the ANOVA of shoot length (1195.53) are presented in Table 1.…”
Section: Shoot Lengthmentioning
confidence: 99%
“…125 Therefore, methods to alter the existing genetic responses to heat are under intensive investigation, such as the use of nanoparticles. 126,127 However, the application of C-dots to mitigate the impacts of heat stress on plants remains a less explored area. In one of the few studies, Wang et al investigated the impact of S. miltiorrhiza-derived C-dots on improving the heat stress tolerance in Italian lettuce plants.…”
Section: Heat Stressmentioning
confidence: 99%
“…During stress, physiological and biochemical changes occur in plant cells that can adversely affect plant growth, development, and productivity ( Al-Ashkar et al, 2019 ; Seleiman et al, 2020b , 2021a ; Taha et al, 2021 ). Species and varieties bred to tolerate these challenges along with nanotechnology and other climate-sensitive agricultural technologies could be the most efficient adaptation strategy to cope with climate and abiotic stress factors, thereby achieving sustainable production ( Kumari et al, 2022 ).…”
Section: Abiotic Stressmentioning
confidence: 99%